EFFECTS OF LEARNING ACTIVITIES APPLIED BY USING LOVE MODEL ON RESPONSIBLE CITIZEN OF NINETH GRADE STUDENTS - Kruon, Yanika; Namsomboon, Manasanan (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aims to 1) study the responsible citizenship of Nineth Grade Students which after from Effect of Learning Activities Applied by Using LOVE Model on Responsible Citizen of Grade 9 Students. The sample was 20 students in Nineth Grade Students room 3/1 at Wang Nam Khiew School, second semester, academic year 2023 which was retrieved from the cluster sampling method. The research instrument was the study plan of citizenship that contained three learning units; Good Citizenship in a Democratic Form of Government with the King as Head of State, Living Together in a Multicultural Society, and Managing Conflict through Peaceful Way and Responsible Citizen Measurement which analyzed data by means and standard deviation and content analysis. The research findings were summarized as follows: The responsible citizenship level of students in Nineth Grade Students after learning through the LOVE Model was a great level.